Counseling older people : opportunities and challenges - Kampfe, Charlene M. (American Counseling Association, 2015)
This book provides insight into the primary issues faced by older adults; the services and benefits available to them; and the knowledge base, techniques, and skills necessary to work effectively in a therapeutic relationship. Dr. Kampfe offers empirically and anecdotally based strategies and interventions for dealing with clients' personal concerns and describes ways counselors can advocate for older people on a systemic level. Individual and group exercises are incorporated throughout the book to enhance its practicality. Topics covered include an overview of population demographics and characteristics; counseling considerations and empowering older clients; successful aging; mental health and wellness; common medical conditions; multiple losses and transitions; financial concerns; elder abuse; veterans issues; sensory loss; changing family dynamics; managing Social Security and Medicare; working after retirement age; retirement transitions, losses, and gains; residential options; and death and dying.